Penggunaan self cleaning Fotokatalis Tio2 dalam Mendegradasi Ammonium (NHd) Berdasarkan lama waktu penyinaran - Ana Hidayati Mukaromah; Muh. Amin; Sri Darmawati (JURNAL KESEHATAN, 2010)
Ammonium is NH a ' ions thdt are not colored, smelly and dangerous to health, its concentrqtion determined by spectrophotometric method. Ammonium which is atkalini when exposed i tignt or heat will cause odor, because the smell of ammonia' generated, needed a technologt to reiuce or eliiinate the levels of ammonium. Problems of this research is what percentage of degrqdalion of ammonium (NH4 +) with 20 mg of photocatalyst TiO 2 based on the exposure time?The general obiective of this research is to study the degradation of ammonium (NH 4 +) with TitaniumDiol<sida photocatalyst (TiO 4 20 mg based on exposureiime 30, 60: g0, 120, 240, 360, 480, 600, 900, 1500 minutes. Special purpose in this study are: Peiform initial optimization siudy is determine the optimum concentration of ammonium that can produce the mmimum percent ammonium degradation with the number of photocatalyst TiO 2 Titanium Dioxide 20 mg durig the time of 120 minutes. Doing degradation of ammonium with ammonium concentrqtion optimim withlhe number of photocatalyst TiO 2 2b mg for varying exposure time 30, 60, 90, 120, 240, 360, 480, 600, 900, I500 minures.The research object is a solution of ammonium produced in the chemical laboratory of the concentration of 100 ppm was reduced to 10, 20, i0, 40 ppm and then determined the optimui concentration of ammonium. Percent degradation of ammonium with an optimum concentration wiih the addition of titanium dioxide photocatalyst TiO 2 20 mg with varying exposure time 30, 60, 90, t 20, 240, 360, 480, 600,-900, t 500minutes each performed three times repetition.The results showed that the optimum concentration of ommonium NHr*) with photocatalytic TiO2 20 mg over 120 minutes is 30 ppm. Degradation of the ion (NHr') with the variation ofradiarion SO, AO, g0, 120, 240, 360, 180, 600, 900, and 1500 minutes with the optimum concentration of 3i ppm of ammonium and the number of photocatalyst TiO 2 20 mg is five consecutive, 66ok, 6.06%, 6.64%, Z.iZbZ, A.Otm, g.64%, g.5g%,10.52%o, ll.0B%, 11.40%. The longer the exposure time the greater the percent degradation of the ion (NH4 +)Keywords: Degradation of ammonium, Tio2 Photocatalyst, Irradiation time.